The Effect of Turmeric Powder Supplementation in Feed on Broiler Chicken Performance - Prastiyo, Dwi Subakti; Anwar, Rohmatul; Asih, Diah Reni; Ahmad, Miftahudin (Open Global Scientific Journal, 2025)
Aims: This study aimed to evaluate the effect of turmeric (Curcuma longa) powder supplementation in the diet on the production performance of broiler chickens, including feed intake, body weight gain, and feed conversion ratio (FCR).Methods: The experiment was arranged in a Completely Randomized Design (CRD) with four treatments: P0 (no turmeric powder), P1 (1% turmeric powder), P2 (2% turmeric powder), and P3 (3% turmeric powder), each with three replications.Results: Statistical analysis showed that turmeric powder supplementation had no significant effect on feed intake (P > 0.05), with average intake ranging from 1262.67 to 1266.33 g/bird. However, turmeric supplementation had a significant effect (P < 0.05) on body weight gain and FCR. The P1 treatment (1% turmeric powder) resulted in the highest final body weight (1172.33 ± 2.01 g/bird) and the lowest FCR (1.0777 ± 0.02), indicating improved growth efficiency and feed utilization. Based on these findings, it can be concluded that turmeric powder supplementation up to 3% in the diet can enhance the growth performance of broiler chickens, with 1% being the most optimal level of supplementation, as there were no significant differences observed among the 1%, 2%, and 3% treatments.